2024
DOI: 10.1038/s41467-024-46945-x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome differences by sex in oncology clinical trials

Ashwin V. Kammula,
Alejandro A. Schäffer,
Padma Sheila Rajagopal
et al.

Abstract: Identifying sex differences in outcomes and toxicity between males and females in oncology clinical trials is important and has also been mandated by National Institutes of Health policies. Here we analyze the Trialtrove database, finding that, strikingly, only 472/89,221 oncology clinical trials (0.5%) had curated post-treatment sex comparisons. Among 288 trials with comparisons of survival, outcome, or response, 16% report males having statistically significant better survival outcome or response, while 42% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…A recent data analysis article reported by Kammula et al in Nature Communications 11 represents a significant response to this urgent research need, which will be studied and applied by oncology field for years to come. This study comprehensively characterised sex outcome comparisons in all oncology interventional clinical trials and identified comparisons that found a significant difference between males and females.…”
Section: Current Landscape Of Outcome Comparisons By Sex In Oncology ...mentioning
confidence: 99%
“…A recent data analysis article reported by Kammula et al in Nature Communications 11 represents a significant response to this urgent research need, which will be studied and applied by oncology field for years to come. This study comprehensively characterised sex outcome comparisons in all oncology interventional clinical trials and identified comparisons that found a significant difference between males and females.…”
Section: Current Landscape Of Outcome Comparisons By Sex In Oncology ...mentioning
confidence: 99%